Sharia legal system and its implementation in Malaysia - Ibnor Azli Ibrahim,; Ahmad bin Muhammad Husni,; Almashaqbeh, Ismail Rashed Abood (Institut Kajian Rantau Asia Barat, 2013)
This study discusses an important aspect of the legal system in the al-risalah era and its implementation in the present time. The important of this research lies in the fact that it uncovers the influence of customs and traditions in society and its assessment in the light of current reality and changes. This study aims at highlighting the legal status of the legal profession, its practices and implementations in the Malaysian courts. This study uses historical and inductive research methodology to collect data and analysis-comparative methodology for analyzing the views and data gathered in order to arrive at conclusions. Among others, this study affirms the importance of the lawyers and the legal system in the Muslims society generally and in the Malaysian society in particular, asserting the necessity not to confine law careers to men only as women have proven their abilities in this area. This study also asserts the importance of having the sharia lawyers appointed by an expert committee.